Intertexts in translation teaching: an example of a humorous text - Kaźmierczak, Marta (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2017)
The paper discusses employing a highly intertextualized text in translator training. Using an example of a humorous story in Russian, the author describes the advantages of the classroom use of such a text. They encompass: facilitating an understanding of the scope of the phenomenon and thus learning to successfully render diverse intertextual signals in varied circumstances, as well as the possibility to formulate and apply a holistic strategy with respect to intertexts. The benefit of enhancing the students’ background knowledge is also emphasized in the context of current curricula.